Registration of 'Liberty' Switchgrass. Issue 3 (9th May 2014) - Vogel, K. P.; Mitchell, R. B.; Casler, M. D.; Sarath, G.
Abstract : 'Liberty' (Reg. No. CV‐271, PI 669371) switchgrass ( Panicum virgatum L.) is a lowland‐type cultivar that is adapted to USDA plant hardiness zones (HZ) 4, 5, and 6 in the U.S. Great Plains and Midwest, east of 100° W. longitude. It was developed for use as a perennial biomass energy crop and is the first high‐yielding biomass‐type lowland cultivar adapted to this region. It can produce greater biomass yields than upland‐ or forage‐type switchgrass cultivars developed previously for use in the region, and it has equivalent winter survival. Liberty has significantly greater winter survival in its adaptation region than previously released lowland switchgrass cultivars such as 'Kanlow' and 'Alamo' that frequently have substantial winter damage and stand loss north of 40° N latitude in the U.S. Great Plains and Midwest.